Laboratory verification of a new high flow differential mobility particle sizer, and field measurements in Hyytiälä. (October 2018) - Kangasluoma, Juha; Ahonen, Lauri R.; Laurila, Tiia M.; Cai, Runlong; Enroth, Joonas; Mazon, Stephany Buenrostro; Korhonen, Frans; Aalto, Pasi P.; Kulmala, Markku; Attoui, Michel; Petäjä, Tuukka
Abstract: Measurement of atmospheric sub-10 nm nanoparticle number concentrations has been of substantial interest recently, which, however, is subject to considerable uncertainty. We report a laboratory characterization of a high flow differential mobility particle sizer (HFDMPS), which is based on the Half-mini type differential mobility analyzer (DMA) and nano condensation nuclei counter (A11), and show the first results from atmospheric observations. The HFDMPS utilizes the state-of-the-art aerosol technology, and is optimized for sub-10 nm particle size distribution measurements by a moderate resolution DMA, optimized and characterized low-loss particle sampling line and minimal dilution in the detector. We present an exhaustive laboratory calibration to the HFDMPS and compare the measured size data to the Hyytiälä long-term DMPS and Neutral cluster and ion spectrometer. The HFDMPS detects about two times higher 3–10 nm particle concentrations than the long-term DMPS, and the counting uncertainties are halved as compared to the long-term DMPS. The HFDMPS did not observe any sub-2.5 nm particles in Hyytiälä, and the reason for that was shown to be the inability of diethylene glycol to condense on such small biogenic particles. Last, we discuss the general implications of our results to the sub-10 nm DMPS based measurements. Highlights: A new high flow (HF) DMPS has been built, calibrated and operated in field conditions for one month. The counting uncertainties of the HFDMPS are reduced by about 50% as compared to the traditional DMPS. The HFDMPS detected about two times more particles than the DMPS in size range of 3–10 nm. Below 3 nm the HFDMPS is currently limited by the inability of diethylene glycol to condense on biogenic particles.